2008
DOI: 10.4103/0255-0857.43558
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of codon usage patterns and identification of predicted highly expressed genes in fiveSalmonellagenomes

Abstract: Purpose: To anlyse codon usage patterns of Þ ve complete genomes of Salmonella, predict highly expressed genes, examine horizontally transferred pathogenicity-related genes to detect their presence in the strains, and scrutinize the nature of highly expressed genes to infer upon their lifestyle. Methods: Protein coding genes, ribosomal protein genes, and pathogenicity-related genes were analysed with Codon W and CAI (codon adaptation index) Calculator. Results: Translational efÞ ciency plays a role in codon us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The differences in evolutionary rates of genes have been adscribed to functional constraints, but a debate is open to clarify the importance of translational costs, reflected in misfolding [47], structural factors [48,49], and even pleiotropy [50], as the factors influencing the evolution of proteins. The compositional and adaptation codon bias in genes are important characteristics of GC-rich organisms, such as the Rhizobiales, because these traits are related to increased expressivity [51-53]. We found that low dN genes had high CAI values (not shown) showing, as others have, that codon bias is a selective force in these genes and a negative correlation of expressivity and evolutionary rates exists [54-56].…”
Section: Discussionmentioning
confidence: 52%
“…The differences in evolutionary rates of genes have been adscribed to functional constraints, but a debate is open to clarify the importance of translational costs, reflected in misfolding [47], structural factors [48,49], and even pleiotropy [50], as the factors influencing the evolution of proteins. The compositional and adaptation codon bias in genes are important characteristics of GC-rich organisms, such as the Rhizobiales, because these traits are related to increased expressivity [51-53]. We found that low dN genes had high CAI values (not shown) showing, as others have, that codon bias is a selective force in these genes and a negative correlation of expressivity and evolutionary rates exists [54-56].…”
Section: Discussionmentioning
confidence: 52%